Primary School Teachers' Views on the Integration of Sustainable Development into Learning - Mustafa Erol (Educational Academic Research)
In this study, we sought an answer to the question of what can be done to integrate sustainable development into learning environments in the context of teacher opinions. We followed a case study design to achieve this goal. The research's study group consists of 15 primary school teachers from northwest Turkey, who were chosen using criterion sampling. We used an interview form to gather research data and analyzed it with content analysis. Teachers think incorporating sustainable development into the learning environment brings many benefits to children. According to findings, sustainable development provided many gains to students. Findings in the context of teacher opinions were: 1) eco-friendly behavior; 2) literacy; 3) awareness of green technologies; and 4) awareness of green professions. In this context, sustainable development should be integrated into primary school curricula. Also, in the study, we emphasize a sustainable education for a sustainable future. In this context, the outputs of sustainable development should be used effectively in education and training environments.